Methylsulfonylmethane alone or in combination with thiocolchicoside modulate autoimmune disease in rats with adjuvant arthritis - AKRAMAS, L.; LEONAVIČIENĖ, L.; BRADŪNAITĖ, R.; VAITKIENĖ, D.; VASILIAUSKAS, V.; DUMALAKIENĖ, I.; ZABULYTĖ, D.; NORMANTIENĖ, T.; JONAUSKIENĖ, I. (Journal of the Hellenic Veterinary Medical Society, 2019)
Many active anti-arthritic natural substances are revealed into the past years. The aim of study was to assess the combined efficacy of methylsulfonylmethane (MSM) with thiocolchicoside (Th) (compound MTh) and MSM alone against adjuvant-induced arthritis (AA) in rats. In the first experiment 30 rats and in the second - 21 ratswere randomly divided into 6 groups: I gr. - AA + MSM (77 mg/kg), II and V gr. - AA + diclofenac (DF), III and VI gr. - the control AA groups without treatment, IV gr. - MTh (38 mg/kg). DF (1 mg/kg) in both experiments was used as a reference drug. 6 rats were as the healthy control group. AA rats were treated from day 0 to 17. All preparations were suspended in 0.5 ml of 1℅ starch gel and injected orally 5 days a week. Body weight and joint swelling were monitored 3 times a week. Development of polyarthritis, blood indices, pro-/antioxidant activity and pro-inflammatory cytokines in blood serum, and histopathology of the liver and paw were assessed at the end of experiment. MSM significantly decreased joint swelling on days 3 and 13. MTh in twice lower dose more markedly suppressed joint swelling and also significantly reduced the changes in soft periarticular tissues, synovium and cartilage as compared to the control AA group. Both preparations alleviated infiltration with inflammatory cells and synovial proliferation, as well as protected cartilage destruction and decreased pannus formation. MSM and MTh improved the blood indices and insignificantly suppressed IL-17. They markedly decreased the level of malondialdehyde (MDA). Some anti-oxidant activity of preparations was also confirmed. No toxic effects on the liver were revealed. MSM and MTh attenuated the development of AA in rats. Combination therapy was more effective than single MSM and required the twice lower doses to receive the beneficial anti-arthritic effect. Both preparations could be the potential preventive or therapeutic candidates for the treatment of autoimmune processes in combination with other drugs.